The Islamic Ideology of Ali Shari’ati (American Journal of Islam and Society, 2010)
It has been thirty years since the Islamic revolution of Iran of 1979, and the name of Imam Khomeini remains alive in the minds of the people as its leader. However, little is known about the contribution of Ali Shari’ati (d. 1977) in awakening the educated youth to realize Islam’s political relevance and to participate in the struggle against the shah’s despotism. The new generation of Iranians know even less about his vision of governance and how it differs from Khomeini’s concept of governance by the ulama. This paper attempts to answer the following questions: Why did Shari’ati appeal to the students and intellectuals? What philosophical and theological elements make up his Islamic ideology, his Islamic sociology, and his concept of struggle (jihad)? How did he manage to blend Shi’ite theology and Marxist dialectical struggle to produce his own brand of Islamic ideology? Is the role of the sociologist to describe or to transform society?